Electrical characteristics of rf-magnetron sputtered BaTa2O6 thin film - Kim, YS; Lee, YH; Sung, MY (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
The characteristics of radio-frequency magnetron sputtered BaTa2O6 thin films with aluminum (Al) top and indium tin oxide (ITO) bottom electrodes have been investigated as a function of applied field and temperature. The optical transmittance in the visible range was in range of 80-90% regardless of the substrate temperature. The dielectric constant increased from 20 to 30 with increasing the substrate temperature and nearly independent of the frequency in the range of 0.3-100 kHz but the loss factors increased with increasing the substrate temperature at high frequency. The leakage currents of BaTa2O6 thin film are in the order of 10(-6)-10(-7)A/cm(2) at the applied field of 1 MV/cm and the charge storage capacitance (epsilon E-breakdown) are 5.64 (100 degrees C), 10.6 (200 degrees C) and 11.8 (300 degrees C) mu C/cm(2). From the deposition temperature, voltage polarity and thickness dependence of leakage current, we can conclude that the dominant conduction mechanism is ascribed to Schottky emission at high electric field (>1 MV/cm) and hopping conduction at low electric field (<1 MV/cm). The Schottky barrier heights measured are 1.14 eV at Al(+) and 0.8 eV at Al(-). (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: LEAKAGE CURRENTS; DEVICES